2012
DOI: 10.1097/hjh.0b013e32834d249a
|View full text |Cite
|
Sign up to set email alerts
|

Plasma levels of matrix metalloproteinases and their inhibitors in hypertension

Abstract: These results suggest that MMP-2, MMP-9 and TIMP-1 may have a role as biomarkers of cardiovascular remodeling in hypertension. If these results are confirmed in prospective clinical studies, they could provide new tools to stratify cardiovascular risk in hypertensive patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
59
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(65 citation statements)
references
References 56 publications
(105 reference statements)
4
59
0
2
Order By: Relevance
“…It is well known that long-term hypertension induces cardiovascular extracellular matrix remodeling. 4,22 Mechanical stretch of the vasculature, as seen in hypertension, induces vascular extracellular remodeling by activation of metalloproteinase-2 and metalloproteinase-9, 23 which both are proteases that play an important role in the degradation of collagen XVIII to endostatin. Moreover, experimental studies show that damages to the vasculature, 24 the myocardium, 25 and the kidneys 26 lead to increased expression of endostatin in these tissues, and that circulating concentrations of endostatin are elevated in patients with prevalent cardiovascular diseases 20,[27][28][29][30] or chronic kidney disease.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is well known that long-term hypertension induces cardiovascular extracellular matrix remodeling. 4,22 Mechanical stretch of the vasculature, as seen in hypertension, induces vascular extracellular remodeling by activation of metalloproteinase-2 and metalloproteinase-9, 23 which both are proteases that play an important role in the degradation of collagen XVIII to endostatin. Moreover, experimental studies show that damages to the vasculature, 24 the myocardium, 25 and the kidneys 26 lead to increased expression of endostatin in these tissues, and that circulating concentrations of endostatin are elevated in patients with prevalent cardiovascular diseases 20,[27][28][29][30] or chronic kidney disease.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a possible explanation could be that increased endostatin mirrors a systemic elevated angiogenic activity, reflecting increased neovascularization induced by vascular, myocardial, or renal ischemia, similar as the role suggested for vascular endothelial growth factor. 4,13,14,[36][37][38] Endostatin has also been shown to exert acute reductions in blood pressure via a release of NO, 39 and individuals with Down Syndrome have significantly higher circulating levels of endostatin and exhibit lower blood pressure compared with control subjects. 40,41 This may indicate that endostatin, per se, may exert a blood pressure lowering effect.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, gelatinases play an important role in vascular remodeling. In human and animal studies, it was demonstrated that increased matrix metalloproteinase-2 and matrix metalloproteinase-9 activity are related with the destruction of the elastic lamina of arteries and the aneurysm formation (9)(10)(11). In patients with hypertrophic cardiomyopathy, it have been suggested that modifications of matrix metalloproteinase-2 and tissue inhibitors of matrix metalloproteinase-2 release and activity can be related or responsible for cardiac remodeling mechanisms (12).…”
Section: Introductionmentioning
confidence: 99%